Pendidikan Agama Islam Dalam Pembentukan Akhlak di SMK Swasta Gebang - Marhan Hasibuan (LPPM Institut Nasional Laa Roiba Bogor, 2019)
Islamic religious education has an important role in the formation of student attitudes and personalities, both in the school environment and in the community. Islamic Religious Education emphasizes the formation of Islamic students' personalities, instills understanding and guides students to have honest, disciplined, good character, and beneficial personalities for others. In general, if students' understanding of Islamic Religious Education is high, then their morals, attitudes and behavior can be categorized as good, and vice versa. The objectives of this research are: to know the process of Islamic religious education in Gebang Private Vocational School, to determine the formation of morality in Gebang Private Vocational School, to determine the formation of morality through Islamic education in Gebang Private Vocational School. This research includes qualitative research. Data collection methods are observation, documentation and interviews. The conclusions in this study are 1. The process of Islamic Religious Education in Gebang Private Vocational School has been going quite well. The process of moral formation in the students of SMK Sawasta Gebang varies, this is based on the level of awareness of different students in following and practicing the results of learning Islamic education in schools. In an effort to form students' morals at Gebang Private Vocational School, an Islamic Religious Education teacher applies several methods, including giving advice, building habits and exemplary.